The Virgin Mary in the Temple of Justice : on how us jurisprudence is messing up argentine constitutional principles - Legarre, Santiago (2014)
Fil: Legarre, Santiago. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina